Using a Bias Potential in a Constant and Pulse Modes for Structural Engineering Vacuum Arc Nanocrystalline Coatings of Zirconium Nitride - O.V. Sobol'; A.A. Andreev; V.A. Stolbovoy; V.F. Gorban; N.V. Pinchuk; A.A. Meylekhov (Журнал нано- та електронної фізики)
In order to develop the direction of "structural engineering nitride coatings" in the work conducted systematic analysis of the impact of the negative bias potential (direct and high-voltage pulse) on the structure, substructure and mechanical properties of ZrN coatings obtained by vacuum arc evaporation. Defined boundary value of (– 100 V) DC potential applied to the substrate, below which a high-voltage pulse potential (– 1200 ... – 2000 V quantity that allows to form peaks bias) makes a decisive contribution to the formation of preferred orientation of the crystallites with the [110] axis. The highest values of hardness 43 GPa are achieved at a constant potential -70 V. Supply high-voltage pulse shifts the maximum hardness in the direction of a greater value of the constant potential.